Antifungal Activity of Lactobacillus sp. Bacteria in the Presence of Xylitol and Galactosyl-Xylitol. (12th May 2016) - Lipińska, Lidia; Klewicki, Robert; Klewicka, Elżbieta; Kołodziejczyk, Krzysztof; Sójka, Michał; Nowak, Adriana
Abstract : Lactic acid fermentation is a natural method of antimicrobial food protection. Antagonistic activity of Lactobacillus sp. bacteria, taking part in this process, is directed mainly against the same or other microorganisms. In this work we determine the impact of the presence of xylitol and galactosyl-xylitol on the antagonistic activity of 60 Lactobacillus sp. strains against indicator molds ( Alternaria alternata, Alternaria brassicicola, Aspergillus niger, Fusarium latenicum, Geotrichum candidum, and Mucor hiemalis ) and yeasts ( Candida vini ). We used double-layer method to select antifungal strains of Lactobacillus bacteria and poisoned medium method to confirm their fungistatic properties. Additionally, we examined the inhibition of Alternaria brassicicola by Lactobacillus paracasei ŁOCK 0921 cultivated with xylitol or galactosyl-xylitol directly on wild cherries. The presence of xylitol and its galactosyl derivative led to increase of spectrum of antifungal activity in most of the studied plant-associated lactobacilli strains. However, no single strain exhibited activity against all the indicator microorganisms. The antifungal activity of Lactobacillus bacteria against molds varied considerably and depended on both the indicator strain and the composition of the medium. The presence of xylitol and galactosyl-xylitol in the growth medium is correlated with the antifungal activity of the studied Lactobacillus sp. bacteria against selected indicator molds.